Study of corroded beam-column joint under cyclic loading - Lim, Jia Hui (Nanyang Technological University, 2020)
This research paper aims to investigate the behaviour of corroded beam-column joint subjected to cyclic loading. Experimental and analytical method will be utilised to conduct an extensive research on the corroded joints. Two exterior joints were casted similarly and adhered to both Eurocode 8 and Eurocode 2 (European Committee for Standardization 2004). The joints were subjected to accelerated corrosion to simulate naturally corroded joints and subsequently tested under cyclic loading. Both joints were targeted to reach a corrosion level of 30%. An axial compressive force ratio of 0.15 was applied to one of the joints whereas an axial compressive force ratio of 0.3 to the other joint. Seismic behaviour such as hysterical response, crack propagation, energy absorption and failure mode of both experiments was recorded and analysed. Both joints experienced beam flexural failure. As drift ratio increases, cumulative energy absorbed by the joint increased exponentially. Modified strut and tie method which incorporates the effects of corrosion was also proposed in this paper to better understand corroded beam-column joint through analytical method. Reduction of bond forces and reinforcement strength was taken into consideration in the model. The modified strut and tie method were then verified with experiments conducted and past experimental observations. Proposed modified strut and tie method showed good agreement with experimental cracks. A parametric study was then carried out to further investigate the behaviour of corroded beam-column joints. Level of corrosion and axial compressive force ratio were varied to analyse the effects on corroded beam-column joints.